2001
DOI: 10.1590/s1519-69842001000400011
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of Parides anchises nephalion (Papilionidae) in a coastal site in Southeast Brazil

Abstract: A population of Parides anchises nephalion was studied during seven months in SE Brazil. The population size was about 10-20 individuals (with theoretic maximum near 60 individuals), with small variations in some months. Sex ratio was male biased, with males dominating in all months. The age structure was not stable, with an increase in new individuals before the population peak in December. The residence time was 14.1 ± 8.2 days for males and 9.0 ± 3.6 to females, with the maximum registered of 30 days. Males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
(16 reference statements)
1
4
0
1
Order By: Relevance
“…This occurrence peak of P. ascanius during spring season (September to December) is a pattern already described for other species of Papilionidae (Brown 1996;Brown and Freitas 2000). Studies on population biology of these butterflies have shown that spring is the season of the year with the highest population density, a reflex to an increase in average temperatures and resources that stimulate the break of the diapause state, common during the winter (Freitas and Ramos 2001;Scalco et al 2016).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This occurrence peak of P. ascanius during spring season (September to December) is a pattern already described for other species of Papilionidae (Brown 1996;Brown and Freitas 2000). Studies on population biology of these butterflies have shown that spring is the season of the year with the highest population density, a reflex to an increase in average temperatures and resources that stimulate the break of the diapause state, common during the winter (Freitas and Ramos 2001;Scalco et al 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Lower proportion of females, observed in some months, may be associated with behavioural and physiological differences, since females are more sedentary and have less longevity (Freitas and Ramos 2001;Herkenhoff et al 2013;Seraphim et al 2018). In addition, females tend to disperse more in search for oviposition sites and, when they produce eggs, they tend to reduce flight time as a strategy to allocate energy for reproduction (Seraphim et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the evolutionary history of the host plant use of Troidini butterflies focused on those species that occur in south‐eastern Brazil, for which almost complete data on host plant use are available, as well as data on host plant secondary compounds (Brown, Damman & Feeny, 1981; Otero & Brown, 1986; Brown et al ., 1991, 1995; Morais & Brown, 1991; Klitzke, 1992; Tyler et al ., 1994; Klitzke & Brown, 2000; Freitas & Ramos, 2001). Table 1 lists all host plants used by the species of New World Troidini studied here, obtained from several literature and field sources.…”
Section: Methodsmentioning
confidence: 99%
“…(1994); 7, Brown et al . (1995); 8, Klitzke & Brown (2000); 9, Freitas & Ramos (2001); 10, F. C. C. Correa (pers. com.…”
Section: Methodsmentioning
confidence: 99%